Türkiye İhracatının 2003, 2004 ve 2005 Yıllarındaki Yüksek Artışının Nedenleri Üzerine Bir Saha Araştırması - (:unkn) unknown (My University, 2006)
Özet: 2001 yılında çıpalı kur rejimin çökmesi ile ihracatta da yeni bir döneme girilmiştir. Dalgalanmaya bırakılan kurlar ihracat kesimi için büyük açılımlar sağlamıştır. 2002 yılı sonlarına kadar dalgalı kur ortamında artışına devam eden kurlar, 2003, 2004 ve 2005 yıllarında takip edilen ekonomik politikaların da etkisi ile ihracat kesimine reel olarak bir katkı sağlamaktan uzak olmuştur. Yüksek kurlardan sipariş alan ihracatçı firmalar ulusal paranın konvertibl dövizler karşısında reel olarak değerlenmesi ile müşteri ve pazarlarını kaybetmemek için çok düşük karlardan ya da başa baş fiyatlardan mal ihraç etmişlerdir. Bu çalışmada, kurlardaki bu olumsuz gelişmeye rağmen ihracattaki yüksek artışların sebepleri bir saha araştırması ile belirlenmeye çalışılmıştır.

Abstract: Due to the collapse of the fixed exchange rate system in 2001, a new era has started in the export. The floating exchange rates regime has facilitated new openings for the exporters' side. The exchange rates which continued to increase in the free floating environment till the end of the year 2002 and the policy that was followed in years 2003, 2004 and 2005 have been far from providing any real contribution to the exporters. During these three years, The exporters which accepted orders at high exchange rates had to export at very low or break-even prices due to the valuation of the national currency against the major convertible foreign currencies. In this study, the reasons of the increase in the export, despite the negative developments in the exchange rates, are analyzed and tried to be clarified with afield work.
A Field Study on the Reasons of the High Increase in Turkey's Export Between the Years of 2003, 2004 and 2005